A model-independent compact dynamical system formulation for exploring bounce and cyclic cosmological evolutions in $$f\, (R)$$ f ( R ) gravity - Saikat Chakraborty; Charlotte Louw; A. S. Agrawal; Peter K. S. Dunsby (European Physical Journal C: Particles and Fields)
Abstract Using the dynamical systems approach together with the cosmographic parameters, we present a model-independent dynamical system formulation for cosmology in f(R) gravity. The formulation is model-independent in the sense that one needs to specify not a particular functional form of f(R) a-priori, but rather a particular cosmological evolution, which fixes the cosmography. In a sense, our approach is the way around the reconstruction method. This is shown using both non-compact and compact dynamical variables. The focus in this paper is on the compact analysis since we demonstrate the applicability of this formulation using examples of bouncing and cyclic cosmology. In particular, our analysis reveals, in a model-independent manner, the problem of achieving such cosmologies when the universe is globally spatially flat and devoid of matter.